Level of Innovation as a Product Development Strategy for MSME Es Dawet Ayu: A Case Study in Ambarawa - Rivanda, Anugrah; Rinova, Dora; Toton (Journal of Business and Halal Industry, 2025)
This research explores the role of innovation in the product development strategy of MSME Es Dawet Ayu in Ambarawa. Using a qualitative descriptive approach, the study involved six key informants, including the business owner, suppliers, producers, distributors, employees, and consumers. Data were gathered through interviews, observations, and documentation. The findings suggest that product innovation in Es Dawet Ayu has been successfully implemented by introducing new flavor variations, utilizing natural ingredients, and improving packaging design. The shift from standard plastic cups to modern bottles and premium packaging has enhanced the product’s hygiene and exclusivity. Additionally, marketing strategies such as social media promotion and special discounts have significantly contributed to expanding the MSME’s market reach and customer base.